Knowledge of Sexual with Anticipation of The Risk of Sexual Violence in Adolescents in Disaster-Prone Areas - Putry Maylinia Utami; Dwi Yati (Jurnal Smart Keperawatan, 2022)
The high number of cases of sexual violence that occur in public and private environments is used as a vigilance for parents and the community, especially adolescent girls who are vulnerable to being targeted by sexual violence. Sexual knowledge is very helpful in providing insight to adolescents to avoid the negative impact of sex and avoid the occurrence of sexual violence. The purpose is to find out knowledge about sexual by anticipating the risk of sexual violence in disaster-prone areas. Research quantitatively with correlational descriptive with a cross sectional approach. The population was 156 respondents at SMA 1 Cangkringan students. Technique proportionate startified random sampling with a sample of 67 respondents, Questionnaire instrument analyzed using Somers'd test. The results showed that most respondents had knowledge of the good category of 49 respondents (73.1%), and most of the respondents had an anticipatory attitude in the good category of 39 respondents (58.2%). And the p-value of 0.000 (p<0.05) with a correlation coefficient value of 0.7 which has a positive relationship or direction. There is a relationship of sexual knowledge with anticipation of the risk of sexual violence in adolescents in disaster-prone areas. Teenagers are expected to always be vigilant and do not be afraid to report to parents or authorities if they experience sexual violence. Keywords: knowledge; sexual violence; adolescent Pengetahuan Seksual dengan Antisipasi Risiko Kekerasan Seksual Pada Remaja di Daerah Rawan BencanaABSTRACT Tingginya kasus kekerasan seksual yang terjadi di ruang publik dan privat dijadikan sebagai peringatan bagi orang tua dan masyarakat khususnya remaja putri yang rentan menjadi sasaran kekerasan seksual. Pengetahuan seksual sangat membantu dalam memberikan wawasan kepada remaja untuk menghindari dampak negatif seks dan menghindari kekerasan seksual. Tujuannya untuk mengetahui pengetahuan seksual dengan antisipasi risiko kekerasan seksual di daerah rawan bencana. Penelitian kuantitatif dengan deskriptif korelasional dengan pendekatan cross sectional. Populasinya adalah 156 responden di SMA 1 Cangkringan. Teknik proporsional startified random sampling dengan jumlah sampel 67 responden, instrumen kuesioner dianalisis menggunakan uji Somers'd. Hasil penelitian menunjukkan sebagian besar responden memiliki pengetahuan kategori baik sebanyak 49 responden (73,1%), dan sebagian besar responden memiliki sikap antisipasi dalam kategori baik sebanyak 39 responden (58,2%). Dan p-value sebesar 0,000 (p<0,05) dengan koefisien korelasi sebesar 0,7 yang memiliki hubungan yang erat atau berarah positif. Ada hubungan antara pengetahuan seksual dengan antisipasi risiko kekerasan seksual pada remaja di daerah rawan bencana. Remaja diharapkan untuk selalu waspada dan tidak takut untuk melapor kepada orang tua atau pihak berwajib jika mengalami kekerasan seksual. Kata kunci: pengetahuan; kekerasan seksual; remaja